ANALISIS BAHAN BAKU AIR MINUM DAN PRODUK OLAHANNYA SERTA ELIMINASI TERHADAP PENCEMARAN HORMON STEROID DAN LOGAM BERAT - L. Mahaputra; SI Zadjuli; M. Ansori; Prihatin .; Sugianto .; Ismudiono .; H Callo (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2010)
Steroid hormone and alloy could contaminate the drinking water which danger to human, because make bad side effect on the health. Steroid hormon may cause diseases ie. malignancy particularly of gen mutation and and heavy alloy may cause discrepancies oforgan among others: lever, kidneys, brain and the others. The objective of this research was to identify quantitatively either steroid sexhormones or heavy metal contaminants in drinking water. The water examination of PDAM, household and mineral water was doneby ELISA method to steroid hormones in Laboratory of veterinary obstetric and endocrine UNAIR .The alloy were analyzed by Atomicabsorption method in Dept. Of Chemistry in ITS laboratory. The data were analyzed by descriptive statistic show that all kinds of drinkingwater samples were not contaminated neither heavy metal such as Cd and Pb nor male sex hormone. But unfortunately contaminationof heavy metal mainly cuprum (Cu) spread it out for all kind of drinking water and its product so then the highest contamination foundin dig-land-water was 87%. The other hand more frequent female sex hormone contaminated drinking water there was estrogen and secondly followed with progesterone hormone. Examination of contaminant steroid hormone in drinking water, water supply of PDAM, Vendors water and mineral water didn’t contaminate with alloy (Cd and Pb) ,also they didn’t contaminate with testoteron hormonehowever almost water reservoir and more over dig-land-water of Mamuju Regency contaminated with Cu more than 0.02 ppm